ACCESS TO IMPROVED HYBRID SEEDS IN GHANA: IMPLICATIONS FOR ESTABLISHMENT AND REHABILITATION OF COCOA FARMS. (23rd March 2016) - ASARE, RICHARD; AFARI-SEFA, VICTOR; MUILERMAN, SANDER
SUMMARY: Poor access to improved seeds in West and Central Africa has compromised crop yields and productivity as most farmers source the bulk of their seeds from informal channels. The use of farmer produced seeds has mostly resulted in high seedling mortality thereby presenting challenges to cocoa rehabilitation programmes across the sub region. With the aid of a mobile data collection system (MDCS), the first of its kind to enhance accuracy of survey results in an improved seed supply system through brokerage and linkages among diverse actors, this study assesses Ghanaian farmers' access to improved hybrid cocoa seeds and provides evidence on the socio-cultural factors that affect field performance of such planting materials. Results show that farmers value a seed brokerage system (SBS), which is facilitated through group bulk purchase, timely acquisition and delivery of seeds. The study also revealed that farm size, land use type and gender have significant effect on survival rate of transplanted hybrid cocoa seedlings over two dry seasons. Regardless of the rehabilitation process, mean survival rate was high (79%) although an 11% ( p < 0.000) difference occurred between gender with men recording a higher rate. The majority of farmers prefer cultivating cocoa on forest and fallow lands, implying continues degradation of forest areas. There is therefore an urgent need for a change of mind set, to advocate for land recycling to spare forest areas to thrive.